Pengaruh Pola Pikir Digital, Ketangguhan Diri, dan Iklim Pertumbuhan terhadap Kemampuan Adaptasi Karyawan pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Utama Belawan - Sri Putri Chairunnisa; Leony Hoki; Hulima Hulima (Institut Nalanda, 2026)
This study aims to analyze the influence of digital mindset, self-resilience, and growth climate on employee adaptability at the Main Harbormaster and Port Authority Office of Belawan. This research used a quantitative approach. The population in this study consisted of all employees at the Main Harbormaster and Port Authority Office of Belawan, with a sample of 75 respondents selected using saturated sampling techniques. Data collection was carried out through questionnaires. The data analysis method used was multiple linear regression analysis with the assistance of SPSS software. The results showed that partially, digital mindset had a positive and significant effect on employee adaptability with a t-count value of 3.114 > t-table 1.994 and a significance value of 0.003 < 0.05. Self-resilience had a positive and significant effect on employee adaptability with a t-count value of 7.572 > t-table 1.994 and a significance value of 0.000 < 0.05. Meanwhile, growth climate had a negative effect on employee adaptability with a t-count value of -2.251 < t-table 1.994 and a significance value of 0.028 < 0.05. Simultaneously, digital mindset, self-resilience, and growth climate significantly affected employee adaptability with an F-count value of 42.084 > F-table 2.73 and a significance value of 0.000 < 0.05. The coefficient of determination value is 62.5%. Based on the research findings, it can be concluded that digital mindset and self-resilience play important roles in improving employee adaptability, while growth climate showed a negative effect on employee adaptability at the Main Harbormaster and Port Authority Office of Belawan.